2023
DOI: 10.1021/acs.est.3c01146
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Dogs and Horses as Sentinels of Per- and Polyfluoroalkyl Substance Exposure and Associated Health Biomarkers in Gray’s Creek North Carolina

Kylie D. Rock,
Madison E. Polera,
Theresa C. Guillette
et al.

Abstract: Central North Carolina (NC) is highly contaminated with per- and polyfluoroalkyl substances (PFAS), in part due to local fluorochemical production. Little is known about the exposure profiles and long-term health impacts for humans and animals that live in nearby communities. In this study, serum PFAS concentrations were determined using liquid chromatography high-resolution mass spectrometry and diagnostic clinical chemistry endpoints were assessed for 31 dogs and 32 horses that reside in Gray’s Creek NC at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Overall, HSA and RSA were quite similar in binding affinities for most PFAS, and our findings suggest that guideline toxicity studies in rat models are not likely to be greatly impacted by species differences in albumin binding for the PFAS congeners in our test set. PFAS have also been detected widely in the tissues of livestock species, including cows and pigs, and are excreted in dairy milk (Guruge et al 2008; van Asselt et al 2013; Numata et al 2014; Death et al 2021; Rock et al 2023). As one of the major routes of exposure to PFAS for humans is consumption of contaminated food and water, assessment of PFAS accumulation in livestock species is also needed to evaluate the role of livestock consumption in human PFAS exposure (Sunderland et al 2019; Roth et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, HSA and RSA were quite similar in binding affinities for most PFAS, and our findings suggest that guideline toxicity studies in rat models are not likely to be greatly impacted by species differences in albumin binding for the PFAS congeners in our test set. PFAS have also been detected widely in the tissues of livestock species, including cows and pigs, and are excreted in dairy milk (Guruge et al 2008; van Asselt et al 2013; Numata et al 2014; Death et al 2021; Rock et al 2023). As one of the major routes of exposure to PFAS for humans is consumption of contaminated food and water, assessment of PFAS accumulation in livestock species is also needed to evaluate the role of livestock consumption in human PFAS exposure (Sunderland et al 2019; Roth et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Per- and polyfluoroalkyl substances (PFAS) are a class of synthetic chemicals, comprising thousands of structurally diverse compounds with at least one fully fluorinated methyl or methylene group (OECD 2021). Due to their stability, persistence, and widespread use, PFAS are ubiquitously detected in biological and environmental matrices (Cousins et al 2020; Guillette et al 2020; Kotlarz et al 2020; Cousins et al 2022; Guillette et al 2022; Kirkwood et al 2022; Rock et al 2023). Some PFAS are toxic to multiple organ systems, including the hepatic, renal, immune, reproductive and nervous systems (Carlson et al 2022; Radke et al 2022; Crawford et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Another sentinel study also conducted in North Carolina on dogs and horses showed that average concentrations of total PFAS in horses were lower than in dogs. The dogs in the study had higher concentrations of PFOS, PFHxS and PFOA than the horses, and the researchers highlighted alkaline phosphatase, glucose and globulin in dogs and gamma glutamyl transferase in horses as potential biomarkers associated with PFAS exposure [105]. Through the various pathways of PFAS release into the environment, the potential risk affects not only terrestrial organisms, but also and especially aquatic organisms, water being the major environmental vehicle for these substances.…”
Section: Animalsmentioning
confidence: 97%